1997-2010年に昭和基地で観測された南極ヘイズ - 原, 圭一郎; 長田, 和雄; 林, 政彦; 矢吹, 正教; 塩原, 匡貴; 森本, 真司; 山内, 恭; K., Hara; K., Osada; M., Hayashi; M., Yabuki; M., Shiobara; et al. (2013)
Remarkable aerosol enhancement phenomena (Antarctic haze) have been observed at Syowa Station, Antarctica, in spite of isolation from the other continents in mid-latitudes. To elucidate seasonal features and vertical features of Antarctic haze, aerosol monitoring data taken by OPC, CPC, and MPL were analyzed in this study. Aerosol enhancement near surface occured twice – eight times a year (mean, 4.4 times a year) in 1997 – 2010. Typical duration of the phenomena was 20 – 60 hrs near surface at Syowa Station. MPL data indicated that aerosol enhancement was identified mostly in boundary layer – lower free troposphere (<2.5 km) and observed slightly in middle troposphere (3 – 5 km). Antarctic haze was often observed druing July through October near surface and upper boundary layer – free troposphere. Relation between aerosol enhancement and gaseous atmospheric species such as CO2, CO, and O3 was also investigated in this study. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object